2014
DOI: 10.1177/1049732314523682
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and Resources of Caregivers of Patients With Incurable Progressive Illness in Sub-Saharan Africa

Abstract: Family caregivers are central to palliative care in sub-Saharan Africa. Yet although supporting caregivers requires a comprehensive understanding of caregiver burden, there has been little research into this topic in Africa. Using the Stress Process Model to investigate the burden experienced by caregivers in South Africa and Uganda, we interviewed 37 caregivers and analyzed the data thematically. Caregivers' primary stressors related to day-to-day patient care and emotional support; secondary stressors includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 25 publications
(34 reference statements)
5
77
0
1
Order By: Relevance
“…Palliative care at EOL in SSA countries can be considered a mixed picture, with most SSA countries without any service, few in various stages of development (mostly on paper plans, or with a few declared professional interest) [ and not as a mainstream public health initiative [18]. In short the situation in SSA countries is one of relative scarcity of palliative care services and resources'.…”
Section: Current Extent Of Palliative Care Practice In Ssa Countriesmentioning
confidence: 99%
“…Palliative care at EOL in SSA countries can be considered a mixed picture, with most SSA countries without any service, few in various stages of development (mostly on paper plans, or with a few declared professional interest) [ and not as a mainstream public health initiative [18]. In short the situation in SSA countries is one of relative scarcity of palliative care services and resources'.…”
Section: Current Extent Of Palliative Care Practice In Ssa Countriesmentioning
confidence: 99%
“…However, studies show that HBC services also include support for other chronic and life-limiting illnesses including cancer (Lindsey, Hirschfeld, Tlou, & Ncube, 2003;Streid et al, 2014). The HBC model incorporates the services of trained healthcare professionals, community-based volunteers, and family members who often play the role of primary carers (Powell & Hunt, 2013).…”
Section: Study Frameworkmentioning
confidence: 99%
“…Caregivers' tension between valuing community support and the stress of visits was reported in a study of caregivers of patients with incurable progressive illnesses in South Africa and Uganda (Streid et al, 2014). A caregiver in the cited study noted that, on one hand, visitors met her needs for social interaction.…”
Section: Communal Caregiving and Resentment Of 'The Other'mentioning
confidence: 99%
“…Furthermore, one should consider that, in addition to being an eminently biological event, it is also part of a social construction influenced by meanings individuals attribute to it and, that directly influence care delivery. 7 Palliative care always targets both patient and family since the family provides and receives care. 2 In this context, there is a primary caregiver, generally a close family member, who assumes the responsibility to care for a dependent patient without any financial compensation, and who often ends up relinquishing his/her own life.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that caregivers experience significant physical, emotional, social, material, financial and existential burden, especially when the care process is prolonged and the disease is in an advanced stage. 2,[7][8] This study is justified by the need for researchers to better understand this context through field research and to identify the specific care needs of this group within the sphere of palliative care, as well as the need for reflection upon the work developed by the FHS based on the integrality and interdisciplinary principles.…”
Section: Introductionmentioning
confidence: 99%